State-of-the-art polyetheretherketone three-dimensional printing and multifunctional modification for dental implants - Chen, Meiqing; Ren, Mei; Shi, Yingqi; Liu, Xiuyu; Wei, Hongtao (Frontiers in Bioengineering and Biotechnology, 2023)
Polyetheretherketone (PEEK) is a high-performance thermoplastic polymer with elastic modulus close to jawbone. PEEK has the potential to become a new dental implant material for special patients due to its radiolucency, chemical stability, color similarity to teeth, and low allergy rate. However, the aromatic main chain and lack of surface charge and chemical functional groups make PEEK hydrophobic and biologically inert, which hinders subsequent protein adsorption and osteoblasts adhesion and differentiation. This will be detrimental to the deposition and mineralization of apatite on the surface of PEEK and limit its clinical application. Researchers have explored different modification methods to effectively improve the biomechanical, antibacterial, immunomodulatory, angiogenic, antioxidative, osteogenic and anti-osteoclastogenic and soft tissue adhesion properties. This review comprehensively summarizes the latest research progress in material property advantages, three-dimensional (3D) printing synthesis, and functional modification of PEEK in the fields of implant dentistry, and provides solutions for existing difficulties. We confirm the broad prospects of PEEK as a dental implant material to promote the clinical conversion of PEEK-based dental implants.